2023
DOI: 10.3390/plants12051136
|View full text |Cite
|
Sign up to set email alerts
|

Orchid Micropropagation Using Conventional Semi-Solid and Temporary Immersion Systems: A Review

Abstract: Orchids, with their astonishingly stunning flowers, dominate the international floricultural market. They are considered prized assets for commercial applications in pharmaceutical and floricultural industries as they possess high therapeutic properties and superior ornamental values. The alarming depletion of orchid resources due to excessive unregulated commercial collection and mass habitat destruction makes orchid conservation measures an extreme priority. Conventional propagation methods cannot produce ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 165 publications
(195 reference statements)
0
3
0
Order By: Relevance
“…This is the first work where the cultivation of L. speciosa in a TIB has been documented. Until now, temporary immersion systems have been used for the cultivation of other orchids, such as Phalaenopsis sp., Vanilla planifolia, Cattleya walkeriana, Dendrobium candidum and Epidendrum fulgens (Nongdam et al, 2023), but not for L. speciosa. Among the advantages of using the TIB are cost reduction and greater simplicity when scaling the process.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This is the first work where the cultivation of L. speciosa in a TIB has been documented. Until now, temporary immersion systems have been used for the cultivation of other orchids, such as Phalaenopsis sp., Vanilla planifolia, Cattleya walkeriana, Dendrobium candidum and Epidendrum fulgens (Nongdam et al, 2023), but not for L. speciosa. Among the advantages of using the TIB are cost reduction and greater simplicity when scaling the process.…”
Section: Discussionmentioning
confidence: 85%
“…The liquid medium employed in this study supported culture for 8 weeks. The successful cultivation of L. speciosa biomass in the TIB can likely be attributed to favorable operating parameters, as factors such as immersion time, medium volume, and photoperiod are known to influence tissue growth in temporary immersion systems (Nongdam et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This causes root injury, leading to poor water and nutrient absorption, and the injuries created are very susceptible to infection by soil pathogens, contributing to the high percentage of mortality after soil transfer. One strategy to minimize root injury is to use a softer medium for rooting the plantlet, as has been done in the micropropagation of Centella asiatica [22], Corema album [23], Capparis spinosa [24], and various orchid species [25]. Results of the rooting experiment showed that the root injury observed in plantlets grown on the semi-solid medium solidified with 4 g/L agar was lower than that observed in plantlets grown on the harder solid medium solidified with 6 and 8 g/L agar.…”
Section: Discussionmentioning
confidence: 99%
“…In order to minimize excessive orchid extraction, artificial propagation techniques of orchid seeds have improved, helping to reduce the demand for wild plants (Nongdam et al 2023). However, drawbacks have been found in the use of artificially grown medicinal orchids, mainly in Asia, where they are considered inferior in quality to ornamental orchids and have a much lower market price than their wild counterparts (Liu et al 2014).…”
Section: Botanical Sciences / Online Firstmentioning
confidence: 99%